2005
DOI: 10.1207/s15327558ijbm1202_4
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, happiness, and health: it’s good to be good

Abstract: Altruistic (other-regarding) emotions and behaviors are associated with greater well-being, health, and longevity. This article presents a summary and assessment of existing research data on altruism and its relation to mental and physical health. It suggests several complimentary interpretive frameworks, including evolutionary biology, physiological models, and positive psychology. Potential public health implications of this research are discussed, as well as directions for future studies. The article conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
358
1
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(418 citation statements)
references
References 53 publications
20
358
1
20
Order By: Relevance
“…Volunteering for a good cause has been shown to be beneficial for one's health and wellbeing (Post, 2005;Meier and Stutzer, 2008;Binder and Freytag, 2013). This beneficial impact also extends to those who work for pay in the non-profit sector, as this paper has…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Volunteering for a good cause has been shown to be beneficial for one's health and wellbeing (Post, 2005;Meier and Stutzer, 2008;Binder and Freytag, 2013). This beneficial impact also extends to those who work for pay in the non-profit sector, as this paper has…”
Section: Resultsmentioning
confidence: 72%
“…Altruistic behavior has been shown in many cases to be associated with good outcomes not only for the recipients but also for those who do good (Post, 2005;Brooks, 2006;Meier and Stutzer, 2008). Giving to charities or volunteering one's time are associated with better health and well-being of the altruist, giving credence to the idea of there being a "warm glow" (Andreoni, 1989(Andreoni, , 1990) that provides the altruist with utility.…”
Section: Introductionmentioning
confidence: 99%
“…Garner and Garner (2011) found a link between individuals' satisfaction with support and intent to remain. More widely, it has been noted that participating in voluntary work is associated with positive feelings for volunteers (Post, 2005), and Tidwell (2005) showed that volunteers who identify with their voluntary employer's vision and values are more satisfied and committed with their volunteering work. These findings resonate with studies on corporate sponsored volunteering, which demonstrate that volunteer involvement leads to beneficial outcomes for the volunteers, the voluntary organization, and the employer who sponsored the volunteering activities (e.g., Booth et al, 2009;Jones, 2010;Rodell, 2013).…”
Section: Outcomes Of Volunteer Engagementmentioning
confidence: 99%
“…Altruism results in positive social inclusion, in distraction from personal problems and self-centred anxiety, in increased wellbeing combined with experiences of meaning and purpose and in a more active lifestyle. People who are involved in helping others generally describe their self-esteem as better than those not involved in such activities (Post, 2005). In a setting where helpfulness is based on altruism, each situation contributes to greater contentment for those involved.…”
Section: Resultsmentioning
confidence: 99%